Avaliação dos achados incidentais pela ressonância magnética da coluna vertebral na população pediátrica e hebiátrica - Daher, Renato Tavares (2020)
Introduction: Incidental findings are common in magnetic resonance imaging (MRI) of the spine because of the high sensitivity of this technique in detecting abnormalities. Few studies to date have evaluated the rate of incidental findings during MRI of the spine in paediatric populations, and none of these studies investigated this topic in the Brazilian population. Objectives: To determine the prevalence of incidental findings in MRI of the cervical, thoracic, and lumbar spine in a paediatric population. Methods: A total of 190 MRI examinations of the spine of patients aged ≤18 years of both sexes were examined. The study included patients with complete medical records who underwent MRI examination of the cervical, thoracic, or lumbar spine, including whole spine sagittal T2. All imaging changes not related to the symptom or indication for MRI were considered incidental findings. Data were analysed using the software STATA/SE version 12.0. Results: Of the 190 MRI examinations, 110 were performed in female patients and 80 in male patients. The mean age of the study population was 12.46 ± 3.68 years. The main clinical indications for MRI in the sample were low back pain, scoliosis, dorsalgia, and cervicalgia. The most common incidental findings were reversal/correction of the normal curvature in the cervical spine; intravertebral disc herniation (Schmorl’s node) and disc dehydration in the thoracic spine; and disc protrusion (twelve cases), intravertebral disc herniation (Schmorl’s node) (five cases), and spondylolysis (four cases) in the lumbar spine. Conclusions: The rate of incidental findings in MRI of the spine in the paediatric population is lower than that in the adult population. Notwithstanding, careful clinical evaluation of pediatric patients with complaints of axial and radiating pain is necessary to determine the correlation between symptoms and imaging findings.